Perception of psychosocial risks in hospitals:: assessment and prevention - BENNOUNA , Aida; BOUGHABA, Assia (Journal of Human Sciences, 2023)
The objective of this study is to carry out a diagnosis of the work situation in terms of psychosocial risks experienced by the nursing staff, to analyze the work situation within the EPH of Touggourt, to identify the psychosocial risk factors in a hospital environment in order to find possible solutions to this situation. To achieve our objective, we used a questionnaire survey distributed to 94 workers. The results show that most of the respondents say they have high demands at work compared to their colleagues in the service. All hospital staff say they work with patients in pain and distress. Also, the respondents state that it is possible to find another better job, because they are dissatisfied with their current job.